Does Happiness Improve Health? Evidence From a Randomized Controlled Trial - Kushlev, Kostadin; Heintzelman, Samantha J.; Lutes, Lesley D.; Wirtz, Derrick; Kanippayoor, Jacqueline M.; Leitner, Damian; Diener, Ed (Psychological Science, 2020)
Happier people are healthier, but does becoming happier lead to better health? In the current study, we deployed a comprehensive, 3-month positive psychological intervention as an experimental tool to examine the effects of increasing subjective well-being on physical health in a nonclinical population. In a 6-month randomized controlled trial with 155 community adults, we found effects of treatment on self-reported physical health—the number of days in the previous month that participants felt healthy or sick, as assessed by questions from the Centers for Disease Control and Prevention’s Behavioral Risk Factor Surveillance System Questionnaire. In a subsample of 100 participants, we also found evidence that improvements in subjective well-being over the course of the program predicted subsequent decreases in the number of sick days. Combining experimental and longitudinal methodologies, this work provides some evidence for a causal effect of subjective well-being on self-reported physical health.